Palmitic acid-modified GnRH-Th epitope peptide immunocastration vaccine (W/O/W adjuvant) can effectively ensure the castration and reduce the smelly smell in boars - Gao, Huayi; Liu, Kun; Zhang, Lu; Wang, Yongfang; Fu, Xubin; Guo, Yujie; Bai, Mei; Shen, Yanbing; Wang, Min (Frontiers in Veterinary Science, 2023)
Recent studies have demonstrated the effectiveness of Gonadotropin-releasing hormone (GnRH) in inhibiting testicular growth and development in male animals to achieve castration while improving the meat quality of various livestock species, including cattle, sheep, goats, and pigs. In this research, a GnRH-Th vaccine was synthesized using the Fmoc solid-phase synthesis technique, and the T helper (Th) antigen was modified with palmitic acid to improve its efficacy. The vaccine was then coated with a water-in-water-water adjuvant to improve stability and safety. After passing safety and stability tests, the vaccine was administered to 13-week-old boars, and the results showed that it was stable, safe, and effective for up to 15 months. Moreover, the vaccine did not negatively affect the growth rate and body weight of the pigs. The palmitic acid-modified "GnRH-Th epitope peptide immunocastration vaccine (Water-in-Oil-in-Water (W/O/W)) effectively reduced the testosterone concentration and achieved castration. The concentration of androstenone and skatole hormones significantly decreased, leading to improved meat quality in the boars. The boars were then slaughtered at 33 weeks of age, and the results showed that the meat quality of the vaccinated boars was superior to that of the non-vaccinated control group (P < 0.05). Overall, this research demonstrates the potential of the palmitic acid-modified GnRH-Th vaccine for achieving effective and safe immunocastration in boars.